Development of a Phage Cocktail to Target Salmonella Strains Associated with Swine - Anisha M. Thanki; Viviana Clavijo; Kit Healy; Rachael C. Wilkinson; Thomas Sicheritz-Pontén; Andrew D. Millard; Martha R. J. Clokie (MDPI AG, 2022)
Infections caused by multidrug resistant Salmonella strains are problematic in swine and are entering human food chains. Bacteriophages (phages) could be used to complement or replace antibiotics to reduce infection within swine. Here, we extensively characterised six broad host range lytic Salmonella phages, with the aim of developing a phage cocktail to prevent or treat infection. Intriguingly, the phages tested differed by one to five single nucleotide polymorphisms. However, there were clear phenotypic differences between them, especially in their heat and pH sensitivity. In vitro killing assays were conducted to determine the efficacy of phages alone and when combined, and three cocktails reduced bacterial numbers by ~2 × 103 CFU/mL within two hours. These cocktails were tested in larvae challenge studies, and prophylactic treatment with phage cocktail SPFM10-SPFM14 was the most efficient. Phage treatment improved larvae survival to 90% after 72 h versus 3% in the infected untreated group. In 65% of the phage-treated larvae, Salmonella counts were below the detection limit, whereas it was isolated from 100% of the infected, untreated larvae group. This study demonstrates that phages effectively reduce Salmonella colonisation in larvae, which supports their ability to similarly protect swine.